Evaluation of t-Butylhydroquinone and Heating Effects on Variation of Fatty Acids of Three Edible Oils by Principle Component Analysis - Abdollahi, A.; Jamshidi, M.; B. Ghasemi, Jahan (Asian Journal of Chemistry, 2011)
Principle component analysis, which is an important method of chemometrics, as a fast and efficient method for evaluating the effect of antioxidant on changing fatty acids in oils during heating, is proposed. Gas chromatography was used for quantitative determination of methyl esters of myristic acid, palmitic acid, srearic acid, oleic acid, linoleic acid and linolenic acid before and after the addition of t-butylhydroquinone during 8 h heating with 1 h periods. The fatty acid composition values and common indices were evaluated by Pearson correlation and principle component analysis. Present results indicates a significant high correlation (p < 0.01) between the heating time and relative percentage of all fatty acids in the presence of antioxidant while the data has lower correlation coefficient in the absence of antioxidant. Principle component analysis results show and confirm that the changing of fatty acids in the presence of antioxidant is smoother. Comparison of the effect of the antioxidant on sunflower, frying oil (based on palmolein) and canola oil by principle component analysis shows that the effect of antioxidant on sunflower oil is stronger than frying oil and canola oil.